A1 Efl Students’ Insights About The Use Of Role- Plays In Two English For Specific Purpose (esp) Courses To Develop Speaking Skills In The Hotel And Tourism Management Career Of a Public University In Ecuador - Espol (2017)
The analysis of this study is expected to show that participants perceive role-plays as an effective technique to improve oral communication skills. For this purpose, the author of this thesis explores the perceptions of two groups of students enrolled in an esp course in the career of hotel and tourism management in an ecuadorian public university. In order to obtain information regarding the use of role-plays to develop speaking skills, the researcher interviews students by using semi-structured questions through focus group discussions and individual interviews in three interventions. There are thirty-five participants who take part in this study. twenty-three students belong to the fifth semester and twelve students to the seventh semester. for the first intervention, nineteen students from the fifth semester participate in the focus group discussion and the twelve students from the seventh semester participate in the individual interview.